2017
DOI: 10.1111/mcn.12476
|View full text |Cite
|
Sign up to set email alerts
|

Availability of breastfeeding peer support in the United Kingdom: A cross‐sectional study

Abstract: Peer support is recommended by the World Health Organization for the initiation and continuation of breastfeeding, and this recommendation is included in United Kingdom (U.K.) guidance. There is a lack of information about how, when, and where breastfeeding peer support was provided in the U.K. We aimed to generate an overview of how peer support is delivered in the U.K. and to gain an understanding of challenges for implementation. We surveyed all U.K. infant feeding coordinators (n = 696) who were part of U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…A key driver for women seeking out social media support groups was a lack of practical support from health professionals and unavailability of peer breastfeeding support services. Given the significant recent cuts in breastfeeding support last year (Guardian, 27/07/, ) exacerbating patchy provision of peer support (Grant et al, ), this is unsurprising. Many health professionals describe how they want to provide the one‐to‐one, in‐depth, and emotional support that women value (Dykes, ), but staffing and resource pressures mean that they do not have the capacity (Burns, Schmied, Sheehan, & Fenwick, ; McInnes & Chambers, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key driver for women seeking out social media support groups was a lack of practical support from health professionals and unavailability of peer breastfeeding support services. Given the significant recent cuts in breastfeeding support last year (Guardian, 27/07/, ) exacerbating patchy provision of peer support (Grant et al, ), this is unsurprising. Many health professionals describe how they want to provide the one‐to‐one, in‐depth, and emotional support that women value (Dykes, ), but staffing and resource pressures mean that they do not have the capacity (Burns, Schmied, Sheehan, & Fenwick, ; McInnes & Chambers, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these benefits, many women report challenges in attending face‐to‐face peer support groups. Due to cuts in funding and services, breastfeeding peer support is not available equally to everyone in the United Kingdom (Grant et al, ). Women can also be reluctant to attend face‐to‐face groups due to anxiety or feeling like a failure (Hunt & Thomson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Health visitors could be better educated about the continued benefits of extended breastfeeding and trained to understand and offer support around some of the psychosocial challenges women who chose to breastfeed beyond six months can face. Peer support has worked very effectively for women earlier at earlier stages of breastfeeding but a recent UK survey showed how provision is very patchy with only 56% of the United Kingdom covered alongside additional concerns around the quality of some provision, integration with formal health and care and under-participation by poorer and more vulnerable women (Grant et al 2018). However some women who wish to breastfeed on a longer-term report moving away from general peer support networks because their choices can be challenged by other mothers.…”
Section: Discussionmentioning
confidence: 99%
“…A survey in 2014 of all known infant feeding co-ordinators in the UK had a 19.5% response rate, and covered of 58% of NHS trust/health board areas. 49 This study identified wide availability of breastfeeding support across the UK, with peer support available in 78% of areas and breastfeeding support groups available in 90% of areas. However, these may not be representative of all areas and the support may be provided only in selected localities within trust/health board areas.…”
Section: Chapter 1 Introductionmentioning
confidence: 93%